Synthesis, characterization, oxygen electrocatalysis and OFET properties of novel mono- and ball-type metallophthalocyanines - BAŞAK, ALİ SADİ; ÖZKAYA, ALİ RIZA (ROYAL SOC CHEMISTRY, 2014)
Novel mono- and ball-type Co(II), Zn(II) and Cu(II) metallophthalocyanines (MPcs) were synthesized from 1,1'-p-anisylidenbis(2-naphthoxyphthalonitrile). The MPcs have been characterized by elemental analysis, UV/Vis, IR and H-1-NMR spectroscopy and MALDI-TOF mass spectrometry. The performances of organic field effect transistors (OFETs) of the dinuclear ball-type MPcs have been compared to those of mononuclear counterparts. The ball-type MPc based OFETs showed a p-channel and typical ambipolar transport properties. On the other hand, it was not possible to measure the full transfer characteristics of the mononuclear MPc based devices. The best results were obtained in the case of dinuclear Cu2Pc2. In this case, the mobility value is mu = 4.4 x 10(-2) cm(2) V-1 s(-1) and the threshold voltage is 27.6 volts. The reduction and oxidation characteristics of the mono-nuclear and ball-type MPcs have been compared by cyclic voltammetry, square wave voltammetry and controlled potential coulometry on platinum in nonaqueous media. The comparison suggested that the ball-type complexes form ring-based and/or metal-based mixed-valence species as a result of the remarkable interaction between the two Pc rings and/or metal centers. The stability of these species was confirmed by the mixed-valence splitting values for the complexes. The electrocatalytic performances of the mononuclear and dinuclear complexes for the oxygen reduction reaction were also studied. The compounds involving Co(II) at the phthalocyanine core, especially the ball-type one, showed much higher catalytic performances towards oxygen reduction than those of the other ones.
Keywords: HETERO-DINUCLEAR PHTHALOCYANINES; FIELD-EFFECT TRANSISTORS; GAS-SENSING PROPERTIES; REDUCTION; PERFORMANCE; UNITS; 1,2-BIS(3,4-DICYANOPHENOXYMETHYL)BENZENE; MECHANISM; CLAMSHELL; BRIDGES